2008
DOI: 10.1002/cbic.200800252
|View full text |Cite|
|
Sign up to set email alerts
|

Tryptophan π‐Electron System Capping a Copper(I) Binding Site—A New Organometallic Bonding Mode in Proteins

Abstract: CORRIGENDUM Parts A and B of the legend to Figure 2 in this article were unfortunately transposed. Part A in fact shows the structure of the h 2-naphthyl-1-aza-2,4,8-dithiacyclodecane Cu I complex, while B shows the cationic complex of Cu I with tridentate N-(3-indolyl-ethyl)-N,N-bis(6-methyl-2-pyridylmethyl)amine. The authors apologise for this error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Considering the more accurate values of the radii for Cu I (1.13 ), Ag I (1.33 ), and Au I (1.25 ), [49][50][51] significant interactions with arenes should show distances of less than 2.83 for Cu I , 3.03 for Ag I , and 2.95 for Au I . This is consistent with the values reported for arene-Ag I complexes, which except for that found in the copper/silver-binding protein, [43][44][45] show a maximum Ag I -C distance of 2.46 . [40] Gold(I) complexes 4 a-d contain a strong Au-arene bond with toluene or p-xylene ligands (bond length < 2.95 ), whereas the interaction with the covering phenyl or anthracenyl groups in complexes 4 a-d and 5 is much weaker (distance > 2.95 ).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Considering the more accurate values of the radii for Cu I (1.13 ), Ag I (1.33 ), and Au I (1.25 ), [49][50][51] significant interactions with arenes should show distances of less than 2.83 for Cu I , 3.03 for Ag I , and 2.95 for Au I . This is consistent with the values reported for arene-Ag I complexes, which except for that found in the copper/silver-binding protein, [43][44][45] show a maximum Ag I -C distance of 2.46 . [40] Gold(I) complexes 4 a-d contain a strong Au-arene bond with toluene or p-xylene ligands (bond length < 2.95 ), whereas the interaction with the covering phenyl or anthracenyl groups in complexes 4 a-d and 5 is much weaker (distance > 2.95 ).…”
Section: Introductionsupporting
confidence: 92%
“…[37][38][39] The Au I -arene bonds in 4 a-d are much shorter than those of related arene-Ag I complexes, [40][41][42] for which Kochi found that the distance parameter d (the separation of Ag from the mean aromatic plane) was invariant at d = (2.41 AE 0.05) , and independent of the hapticity (h 1 or h 2 ), hybridization, or multiple coordination. [40] Ag I -and Cu I -arene bonding play an important role in the metal transport by the periplasmatic copper/silver-binding protein (CusF), [43][44][45] in which a tryptophan amino acid binds to Ag I or Cu I by h 2 coordination with the C4 À C5 bond of the indole ring (2.67/2.86 for Cu I and 2.99/3.29 for Ag I ). A tighter coordination of Cu I with the C2ÀC3 indole bond (2.23 and 2.27 ) has been shown in N-(3-indolylethyl)-N,Nbis(6-methyl-2-pyridylmethyl)amineÀCu I .…”
Section: Introductionmentioning
confidence: 99%